Avaliação dos efeitos da Suplementação do Ácido Graxo ômega 3 em modelo de tumor de mama murino e mucosite induzida por 5-Fluouracil - Aline Luiza Afonso de Souza (2020)
Omega 3 is a polyunsaturated fatty acid used as a therapeutic agent in the treatment of various diseases. It is widely accepted that its use can exert an anti-inflammatory effect. Thus, it would be interesting in the prevention and treatment of mucositis, which is described as an inflammation that affects mucosal membranes from the mouth to the anus, due to the use of chemotherapy and radiotherapy. Patients who suffer from this outcome, usually presents weight loss, anorexia and odynophagia,also there is an increased risk of bacterial translocation, due to the increase of the intestinal permeability (IP). Such complications can lead to the interruption of chemotherapy treatment until the patient is recovered. Previous work has shown that omega 3 was able to reduce weight loss and reduce IP by reducing intestinal cell apoptosis. However, the effects of omega 3 supplementation from the diet on the tumor remains unknown. This study aimed to investigate the effect of this compound on chemotherapy-induced mucositis in the murine breast tumor model. For that, BALB/ c mice were divided into the control (CTL), tumor control (CTLTU), omega 3 tumor (TUW3), 5-fluouracil tumor (TU5FU) and 5-fluouracil omega 3 tumor (TU5FUW3) groups. Tumor cells were inoculated (day 1) and, since they were already palpable (day 10), groups TUW3 and TU5FUW3 started receiving the chow supplemented with omega 3 for 10 days, while the other animals received control chow. At the end of this period, animals from groups TU5FU and TU5FUW3 received an intraperitoneal injection of 5-FU (300mg / kg) to induce mucositis, while the other animals received an injection of saline. After 72 hours, all animals were euthanized for data collection. Omega 3 supplementation was not able to prevent weight loss due to mucositis. However, animals from TU5FUW3 group showed a reduction in IP by recovering the tight-junctions ZO-1 and occludin, and by preventing the mucosal damage. Animals from CTLTU group also showed increased PI and reduced expression of tight-junction proteins, probably due to the release of cytokines TNF-α and IL-1β, according to their dosage in the spleen. In addition, our results have demonstrated that animals supplemented with omega 3, have shown a reduction in the size of the tumor and the number of metastasis in lungs. We have found that the reduction was mediated through a reduction in the proliferation of tumor cells and also by an increased affinity of tumor cells to the chemotherapeutic drug, leading to their apoptosis. This selective cytotoxicity process leads to the reduction of liver toxicity. Given these results, we can conclude that omega 3 supplementation, for ten days, was able to attenuate the effects of chemotherapy-induced mucositis, without causing damage to its antitumor activity.